TWO-PHASE ANAEROBIC DIGESTION OF FOOD WASTE AT BATCH MODE UNDER MESOPHILIC TEMPERATURE - FADZIL, FARIHAH (2023)
The alarming environmental issue of the landfill is the harmful greenhouses gases (including methane) as a result of decomposition of the organic waste (including food waste,FW). The anaerobic digestion (AD) is better in managing organic waste because it is a closed system. Moreover, AD is the producer of renewable energy. A single phase or two-phase setup can be used to operate AD. But, Two-phase AD (TPAD) have some advantages over single phase AD (SPAD) systems in terms of selection of microorganisms and process efficiency. This study aims to evaluate the hydrogen and methane potential of FW slurry (FWS) via TPAD. FWS was used due to smaller particle size than solid FW which smaller particle size increases the surface area available to the anaerobic microorganisms. Biochemical hydrogen potential (BHP) test and biochemical methane potential (BMP) tests were conducted in batch mode and monitored continuously using AMPTS II for 7 days and 23 days respectively. The BHP test fed by FWS prepared at initial pH of 5.5. Then the BMP test was continued in which the effluent BHP. The BMP tests were conducted at I/S ratio of 2.0 and 3.0, each with an initial pH of 8.0. Both BHP and BMP tests were at a mixing speed of 60 rpm and operated at 35 ± 1°C. In BHP test, the findings show that the ultimate hydrogen production and hydrogen production rate were 899.44 mL H2/gVS and 537.22 mL H2/gVS day, respectively. While in BMP test, the ultimate methane yield and methane production rate observed at I/S of 3.0 increased by 59% and 47% as compared to I/S of 2.0 respectively. Modified Gompertz modelling was found to be the best fit for laboratory data (BHP and BMP), indicated by the linear regression (r2) and percentage different between laboratory and modelling analysis. In conclusion, food waste slurry (Malaysia dietary) was able to produce renewable energy. Despite that, the methane potential is much higher as compared to the hydrogen potential. Food waste is the recommended substrate for the renewable energy plant feedstock portfolio diversification solely for hydrogen or methane.